Islamic Boarding School Education in Forming Santri Competence at Azzainiyyah Islamic Boarding School High School - Asy'ari, Hasyim; Hasanah, Mizanul; Sawitri, Sona (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This paper aims to reveal the uniqueness of the curriculum management of Azzainiyyah High School which is under the auspices of Azzainiyyah Islamic Boarding School. The curriculum is an important component in the education system, recording the stages and procedures to achieve educational goals. The existence of pesantren as an educational institution is seen through the quality of its graduates. Curriculum management is designed as a reference to maintain and produce graduates who are in accordance with the planned objectives, integrating formal education and boarding school to produce students who excel in various aspects of life.This research uses qualitative research with a case study approach. The data collection method is through interviews, observation and documentation. The data analysis used the Miles Hubarmen & Saldana model. The curriculum management of Azzainiyyah High School is designed based on the vision of the founders of the boarding school, with annual updates without changing the basic formulation. The curriculum integrates formal and boarding school education, adopting the distinctiveness of boarding schools that strengthen academic and spiritual learning. The main focus of the curriculum is to produce santri with four main competencies: high knowledge, Sufi character, independent life, and true leadership. These four competencies become the basic philosophy that shapes all educational units at Azzainiyyah Islamic Boarding School, designed to produce individuals who excel in various aspects of life, both academically, spiritually, and socially.